2014
DOI: 10.1007/s00330-014-3299-2
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial dysfunction in type 2 diabetes mellitus: insights from cardiac MRI

Abstract: Objectives The left atrium (LA) modulates left ventricular filling through reservoir, conduit and booster pump functions. Only limited data exist on LA involvement in type 2 diabetes mellitus (DM2). This study sought to assess LA function in asymptomatic DM2 with cardiac MRI. We hypothesized that cardiac MRI can detect LA dysfunction in asymptomatic DM2. Methods Forty-five patients with asymptomatic DM2 and 24 normoglycaemic controls were studied. MRI cine imaging was performed to measure LA maximal and minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 28 publications
3
31
0
1
Order By: Relevance
“…Insulin resistance is a main element of MetS, linked with several pathogenetic defects that can lead to heart failure and CV mortality 36. This result is consistent with a previous magnetic resonance imaging study accounting a relationship between type 2 diabetes and impaired LA ejection fraction 37. This result is consistent with a previous magnetic resonance imaging study accounting a relationship between type 2 diabetes and impaired LA ejection fraction 37.…”
supporting
confidence: 90%
“…Insulin resistance is a main element of MetS, linked with several pathogenetic defects that can lead to heart failure and CV mortality 36. This result is consistent with a previous magnetic resonance imaging study accounting a relationship between type 2 diabetes and impaired LA ejection fraction 37. This result is consistent with a previous magnetic resonance imaging study accounting a relationship between type 2 diabetes and impaired LA ejection fraction 37.…”
supporting
confidence: 90%
“…29,36 In our study, diabetic rats showed asymptomatic cardiac dysfunction manifested as significant reductions in heart rate (HR), left ventricular eject fraction (LVEF), stroke work (SW) and cardiac output (CO), left ventricular F I G U R E 4 Nrf2/p62 signalling pathway played the key role in the ALP protection to high glucose-induced cardiomyopathy. We showed that reductions in cardiac nuclear translocation of Excessive oxidative stress induced by hyperglycaemia is a major mechanism of DCM and the subsequent cardiac dysfunction both in human and in animal models of diabetes.…”
Section: Discussionmentioning
confidence: 71%
“…Increased left atrial volume is a marker of diastolic dysfunction, and these patients have been shown to have higher rates of cardiovascular events, including atrial fibrillation, stroke, heart failure, hypertension, and all‐cause mortality . In patients with type 2 diabetes mellitus, left atrial dysfunction has been found to be significantly greater than controls …”
mentioning
confidence: 99%
“…2 In patients with type 2 diabetes mellitus, left atrial dysfunction has been found to be significantly greater than controls. 3 While vitamin D deficiency is typically thought to involve the musculoskeletal system, there has been significant evidence linking it with adverse cardiovascular events. 4 In the Framingham Offspring Study, individuals with vitamin D deficiency (25(OH)D3 < 37.5 nmol/L) had a hazard ratio of 1.62 for development of cardiovascular disease compared with those with normal levels.…”
mentioning
confidence: 99%